Scale or fail : how to build your dream team, explode your growth, and let your business soar - Maslan, Allison (John Wiley & Sons, Inc., 2019)
Scaling a business is not for the faint of heart. It's a mind-bending journey that causes millions of business owners around the globe to either throw in the towel--or avoid risk entirely and suffer from smallness and mediocrity. Most of these businesses fail because they are ill prepared to face the real challenges involved in scaling. Either they don't have the bandwidth to keep up with the sales demand or production, miss out on major opportunities due to fear, or keep making the same mistakes over and over because systems and processes aren't in sync with the rate of growth. To truly scale, you must upsize your strategic practices, implement new marketing strategies, find new ways to build your team, and expand your mindset to break through whatever is keeping you stuck at the same level. Then you must be willing to take the leap into the giant unknown - to make your impossible possible. In Scale or Fail, author Allison Maslan--who has successfully scaled ten companies from scratch and has guided thousands of small businesses to do the same--shares her revolutionary SCALEit Method ® for successfully growing, replicating, and expanding your business. She also shares pivotal mindset strategies she's used to break the fear barrier as a trapeze artist so you can move past any obstacle, take strategic Big Picture risks, and fulfill your dreams of business expansion and skyrocketing profit. Featuring a wealth of real-life success stories, visual tools, and exercises that are prescriptive and inspirational, Scale or Fail offers proven scaling strategies and a proactive approach to: Create your Big Picture Vision and build a plan to achieve it Produce an ever-flowing stream of cash flow with consistent profits Establish a powerhouse team that functions well without you Become a true leader and feel like you deserve your success Improve systems and processes that facilitate scaling Get past the mental and strategic pitfalls that cause revenue bottlenecks Scale or Fail is adaptable to any type of business--manufacturing, consumer goods, a brick and mortar, a digital service, a wholesaler, a consulting service, and everything in between. Whether you're six figures and scaling to seven. . . or in the seven figures and scaling to eight or even nine, Scale or Fail provides the roadmap to multiply your business growth--and empower you to soar in the air with the greatest of ease.